2012
DOI: 10.1165/rcmb.2011-0237oc
|View full text |Cite
|
Sign up to set email alerts
|

MEK-ERK Pathway Modulation Ameliorates Pulmonary Fibrosis Associated with Epidermal Growth Factor Receptor Activation

Abstract: Pulmonary fibrosis remains a significant public health burden with no proven therapies. The mitogen-activated protein kinase (MAPK)/MAPK kinase (MEK)/extracellular signal-regulated kinase (ERK) signaling cascade is a major pathway controlling cellular processes associated with fibrogenesis, including growth, proliferation, and survival. Activation of the MAPK/ERK pathway is detected in the lungs of human fibrosis samples; however, the effect of modulating the pathway in vivo is unknown. Overexpression of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 48 publications
7
112
0
Order By: Relevance
“…Similar to our findings in isolated lung mesenchymal cells, we observed a significant reduction in the intensity of S6 phosphorylation in the total lung lysates of CCSP/TGF-a/S6K2 2/2 mice compared with control, CCSP/TGF-a WT, and CCSP/TGF-a/S6K1 2/2 mice, with no differences in phosphorylated Akt expression (Figure 4). The dampened increase in Akt and S6 phosphorylation between control and CCSP/TGF-a groups seen at 8 weeks of Dox is consistent with previous work showing diminished phosphorylation of signaling intermediates of the PI3K/mTOR pathway after continuous and prolonged TGF-a expression in the lung (23). Together, these findings show differential responses in vivo between the p70S6K isoforms in downstream S6 phosphorylation and proliferative responses in fibrotic lesions.…”
Section: /S6k2supporting
confidence: 90%
See 2 more Smart Citations
“…Similar to our findings in isolated lung mesenchymal cells, we observed a significant reduction in the intensity of S6 phosphorylation in the total lung lysates of CCSP/TGF-a/S6K2 2/2 mice compared with control, CCSP/TGF-a WT, and CCSP/TGF-a/S6K1 2/2 mice, with no differences in phosphorylated Akt expression (Figure 4). The dampened increase in Akt and S6 phosphorylation between control and CCSP/TGF-a groups seen at 8 weeks of Dox is consistent with previous work showing diminished phosphorylation of signaling intermediates of the PI3K/mTOR pathway after continuous and prolonged TGF-a expression in the lung (23). Together, these findings show differential responses in vivo between the p70S6K isoforms in downstream S6 phosphorylation and proliferative responses in fibrotic lesions.…”
Section: /S6k2supporting
confidence: 90%
“…Our previous studies examining the progression of subpleural fibrosis in the TGF-a transgenic model confirmed that selective pharmacologic inhibition of the mTORC1, mitogen-activated protein kinase (MAPK), or PI3K pathways reversed or prevented the progression of the subpleural lesions (14,15,22,23). Pharmacologically targeting the p70S6K is a logical target, as it may represent a crucial converging downstream pathway of these known fibroproliferative signaling pathways that regulate subpleural fibroproliferative disease.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…This model illustrates the importance of regulatory crosstalk between lung epithelial cells and mesenchymal cells. For example, the overexpression of TGF-a in the lung epithelium results in a persistent up-regulation of the mitogen-activated protein kinase kinase (MEK)/extracellular regulated kinase signaling pathway in lung mesenchyme (69). When the inducible expression of TGF-a is discontinued, lung remodeling is partly reversed, allowing for studies of the mediators involved in this reversal process (67).…”
Section: Tgf-a Overexpressionmentioning
confidence: 99%
“…Under physiological conditions, EGFR signaling drives wound healing, and controlled activity of EGFR by HB-EGF has been proposed as a therapeutic approach to prompt and accelerate cutaneous wounds healing (161,363). Of note, aberrant EGFR activation is known to promote fibrosis in tissues such as lung, heart, and pancreas (128,214,229,245). EGFR activity has been implicated in the progression of malignancies such as colon and lung cancer (94,134,314).…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%